Relationship Of Age, Education, Mom's Knowledge About Implant Contraception With The Use Of Implant Contraception In Puskesmas Silinda In 2021 - Pratiwi Lumbantobing; Yuni Vivi Santri P; Susi Amenta Beru Perangin angin (Pena Cendekia Insani, 2022)
The contraceptive program that is promoted and effective is the long-term contraceptive method (MKJP) with implants being one of the leading methods. The percentage of the number of family planning participants who reported no significant change was from 60% in 2006 to 61% in 2014 (BKKBN, 2013). The results of a preliminary survey conducted at the Silinda Health Center obtained information that the total number of family planning acceptors who became implant contraceptive acceptors was still very small, around 15% of the total family planning acceptors who used other contraceptive methods due to fear and lack of knowledge about the benefits of implants. The purpose of this study was to determine the relationship between age, education, knowledge of mothers about implant contraceptives and the use of implant contraceptives at the Silinda Health Center in 2021. The type of research was an analytical survey with a cross sectional approach. The population is pregnant women of all women of childbearing age totaling 95 people with a total sample of 49 people with accidental sampling technique using a questionnaire. Data analysis used chi square test at a significance level of 95%. The results showed that the relationship between maternal age and the use of contraceptive implants using the formula x2 (chi square) with p value = 0.133 (p > 0.05), which means that there is no relationship between maternal age and the use of implant contraceptives, the relationship between maternal education and contraceptive use. implant using the formula x2 (chi square) with p value = 0.154 (p > 0.05) which means that there is no relationship between maternal education and the use of implant contraceptives, and the relationship between mother's knowledge and the use of implant contraceptives using the x2 (chi square) formula with p value = 0.001 (p > 0.05) which means that there is a relationship between mother's knowledge and the use of implant contraceptives. It was concluded that only the knowledge variable had a relationship with the use of implant contraceptives. It is expected that health workers at the Silinda Health Center will provide more information about implant contraceptives to women of childbearing age.